IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS XI PADA MATA PELAJARAN MATEMATIKA - Saputri, Nurlinda Dian (Universitas Sultan Ageng Tirtayasa, 2023)
Problem Based Learning or PBL is an innovative learning model where when carrying out learning activities in class, students are required to actively participate in learning. This research was carried out with the aim of increasing the motivation and active learning of class XI vocational school students in mathematics subjects through Problem Based Learning. This research is a type of Classroom Action Research using the Kemmis and Mc model. Taggart (1990) which consists of four components, namely action planning, action, observation and reflection. This research was carried out in 2 cycles, each cycle consisting of 2 meetings. The subjects of this research were students of SMK Kesatrian Purwokerto class XI DKV 2 with a total of 36 students consisting of 19 men and 17 women. Before the action, initial pre-action data was obtained, where the average student learning motivation was 40.8% and the average student learning activeness was 41.2%. The results of the first cycle of action, learning motivation was 51% and learning activeness was 51.16%. The results of cycle II, learning motivation was 65% and learning activeness was 79.86%. There is a difference in increasing learning motivation in cycles I and cycle II, namely 14% and a difference in increasing students' learning activity, namely 28.7%. So it can be concluded that the implementation of Problem Based Learning can increase the motivation and active learning of class XI SMK students in mathematics subjects